Collection of experimental data for multiaxial fatigue criteria verification. Issue 1 (23rd July 2019) - Morettini, Giulia; Braccesi, Claudio; Cianetti, Filippo; Razavi, Seyed Mohammad Javad; Solberg, Klas; Capponi, Lorenzo
Abstract: The present paper aims to propose data from incisive multiaxial fatigue experimental tests which results from the analysis of several works within current literature. Approximately 200 experimental datasets have been collected and paired with the widest variety of materials and stress combinations. Furthermore, we carried out a critical analysis of the methods with which said datasets were obtained, also focusing on the kind of tests that were conducted, the type of specimens used, modes of data cataloging, and some other aspects which we will further analyze during the discussion. We will only refer to data which come from primary sources, avoiding data transcription errors. We thus created a unified data collection useful for all multiaxial reduction methods verification for ductile materials.